Determinan perilaku penggunaan rokok elektrik / vape pada mahasiswa teknik mesin di universitas pembangunan nasional veteran jakarta: The use of electric cigarette behavior in mechanical engineering students of universitas pembangunan nasional veteran, jakarta - Pranasari, Sitaresmi; Ratnawati, Diah; Tobing, Duma Lumban (Bali Medika Jurnal, 2021)
E-cigarettes are a form of modification from conventional cigarettes to e-cigarettes, a renewal of the type of cigarette that converts liquid into vapor. Student vaping behavior is often found in various campus environments. This study aims to determine the behavioral determinants of the use of e-cigarettes or vapes in students of the Mechanical Engineering Study Program, Universitas Pembangunan Nasional Veterans Jakarta. This research uses cross sectional with quantitative research type using Chi Square for univariate and bivariate variables. The results of the bivariate analysis in this study are the age variable associated with the use of e-cigarettes (p-value = 0.000) and vape user behavior (p-value = 0.039) The p-value of the variable is smaller than the alpha value so that there is a relationship between age and attitude. with vaping behavior in Mechanical Engineering students at the Veterans National Development University, Jakarta. While the unrelated variables were gender (p-value = 1,000), monthly allowance (p-value = 0.142), knowledge (p-value = 0.135), family support (p-value = 0.341), friend support (p - value = 0.808), and smoking-free local regulations (K-value) (p-value = 0.555) where the p-value variable is greater than the alpha value so that there is a relationship between gender, monthly money, assistance, family support, friend support -friends and regulations on smoke-free areas with the topic of using electricity for Mechanical Engineering students at the National Veterans Development University, Jakarta. The conclusion of this study is that there is a relationship between age and attitude towards the behavior of e-cigarette users so that motivation and references are needed in reducing the number of e-cigarettes consumed and students should be able to stop smoking.